Parents' Perceived Behavior Problems in the Persons With Mental Retardation: An Analysis for Parents' Need - Jalan, Rekha Kumari; Adhikari, Jyoti; Belbase, Mohan; Khan, Tanveer Ahmad; Gupta, Veena; Sinha, Uday K. (Journal of Nepalgunj Medical College, 2017)
Background: Mental retardation is a commonly diagnosed developmental problem among psychiatric disorders. Parents frequently report behavior problem in their children with mental retardation and seek help. Aim: Aim of this study is to analyze the behavior problems and their relation with severity, age and sex in the people with mental retardation. Methods: The study included seventy cases of mental retardation with reported behavior problems coming to the Clinical Psychology unit of Nepalgunj Medical College, from March 2013 to February, 2015. The parents' interviewed with regard to behavioral problems in their children of mental retardation was analyzed in twelve areas in terms of severity, age and sex. Results: Disobedience predominates in mild form (22.73%) and in moderate (19.15%), in severe category physical harm towards others (16.67%) and odd behavior in both severe (16.67%) and profound (20.00%) cases of mental retardation. In terms of sex, disobedience predominates in the males (17.70%) and physical harm towards others (17.86%) in females. Disobedience (14.71%) and repetitive behavior (14.71%) are prominent up to six years of age, physical harm towards others (18.46%) in age group 6-12 years, and disobedience (21.43%) predominates between age 12 to 18 years and also above 18 years. Discussion: Our finding are similar with various other studies, except self injurious behavior is more in mild to moderate group of cases than in severe or profound group. Conclusion: Parents predominantly seek help for managing problems of disobedience followed by physical harm towards others and odd behaviors. Journal of Nepalgunj Medical College Vol.13(1) 2015: 8-12